2019
DOI: 10.1021/acs.jafc.9b04318
|View full text |Cite
|
Sign up to set email alerts
|

New Acylated Phenolic Glycosides with ROS-Scavenging Activity from Psidium guajava Leaves

Abstract: Reactive oxygen species and subsequent oxidative stress are reported to play important roles in chronic metabolic diseases. Plant-derived polyphenols, especially food-derived phenolics, have attracted a lot of attention due to their potential usage against oxidative stress-related diseases. The leaf of Psidium guajava (known as guava) is regarded as a good resource of polyphenols and its products are commercially available in Japan as functional foods against multiple chronic metabolism disorders. In the cours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Finally, both of the studies focussing on antioxidant activity several glycosides with significant antioxidative bioactivity (Dissanayake et al, 2017; Li et al, 2019). Furthermore, the level of antioxidant activity shown by some of the isolated glycosides was comparable to or exceeded that of the positive controls (ascorbic acid and minocycline).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, both of the studies focussing on antioxidant activity several glycosides with significant antioxidative bioactivity (Dissanayake et al, 2017; Li et al, 2019). Furthermore, the level of antioxidant activity shown by some of the isolated glycosides was comparable to or exceeded that of the positive controls (ascorbic acid and minocycline).…”
Section: Discussionmentioning
confidence: 99%
“…41 Previous studies, including our group work, has reported that GUB is the major phenolic component present in guava. 18,27 The HPLC−DAD-MS analysis revealed that most phenolics including guavinoside B, flavonoids, 17 and oleuropeic acid-conjugated phenolic glycosides 34 in guava leaves were successfully removed from TGL (see Supporting Information Figure S4). This was supported by the analysis of the ratio (1:29) between total phenolics (2.1%) and total triterpenoids (58.6%) in TGL, which suggested that the enrichment of triterpenoids in guava leaves was achieved.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…guajava leaves with a voucher number No. 1610056 were collected and identified as previous report . Air-dried and powdered P.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…-Fig. aeswilflavonoside IID (7) have been found only in four species including Psidium guajava [25], Eucalyptus cypellocarpa [26], E. resinifera [27], E. maideni [28], and E. polybractea [29], all belonging to the family Myrtaceae. Flavonoid glycosides with a 5-[2-(carboxymethyl)-5-oxocyclopent-yl]pent-3-enylate residue like aeswilflavonoside IC (3) appears also quite rare.…”
Section: Accepted Manuscriptmentioning
confidence: 99%